Studies in eighteenth - century diplomacy 1740 - 1748 - Lodge, Richard (London, 1930)
THIS book has grown rather than been deliberately made. For the last fifty years I have lectured off and on, and for many of them on rather than off, on the relations of the European States to each other during the eighteenth century. And author took one part of those relations as the subject of my Ford Lectures in the University of Oxford. My experience as a teacher has convinced me that the darkest spot in the history of Europe in the eighteenth century is the period of the war of the Austrian Succession. Its military side may have been adequately treated by Carlyle and other writers, but I do not profess to be a military historian. But the political side of the war has been left, at any rate in this country, in great obscurity. The most notable attempts to pene trate this obscurity have been made by Arneth, in his monumental work on Maria Theresa, and by the Duc de Broglie, in the long series of volumes which he has devoted to this period.
Keywords: Diplomacy